Implementasi Kursus Calon Pengantin Berbasis Web Dalam Mengurangi Tingkat Penceraian - Slamet Widodo; Herlambang Brawijaya; Samudi Samudi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Marriage is a spiritual bond between a man and a woman to form a happy and eternal home or family based on the Godhead. Nevertheless, many divorces still occur in the community today. Suscatin is a solution provided by the Government to overcome divorce which is getting higher every year. But there are still obstacles in the organization of Suscatin. The Suscatin implementation is still done manually, where to conduct the exam the bride and groom write on a piece of paper. In addition, the implementation was carried out on the effective day, so the bride and groom could not attend. For this reason, this research was conducted to design a web-based learning system that can facilitate the Office of Religious Affairs and prospective brides. So that the material about marriage can be studied without any obstacles both in terms of time and place of implementation. It is expected to be able to anticipate disputes and divorce as well as violence in the family in order to create a sakinah, mawaddah, and rahmah family